2013
DOI: 10.1016/j.jcomdis.2012.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Temperament, speech and language: An overview

Abstract: The purpose of this article is to discuss definitional and measurement issues as well as empirical evidence regarding temperament, especially with regard to children's (a)typical speech and language development. Although all ages are considered, there is a predominant focus on children. Evidence from considerable empirical research lends support to the association between temperament, childhood development and social competence. With regard to communication disorders, extant literature suggests that at least c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 112 publications
3
64
0
5
Order By: Relevance
“…For example, as Conture et al (2013) suggested, the "directionality of effect" regarding emotion and stuttering (e.g., emotion → stuttering vs. emotion ← stuttering) continues to remain unclear. It is also unknown, in this mixed sample of young children (i.e., some participants will and some will not recover from stuttering), whether those who persist exhibit more positive than negative emotional reactivity (or vice versa) compared with those who recover.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, as Conture et al (2013) suggested, the "directionality of effect" regarding emotion and stuttering (e.g., emotion → stuttering vs. emotion ← stuttering) continues to remain unclear. It is also unknown, in this mixed sample of young children (i.e., some participants will and some will not recover from stuttering), whether those who persist exhibit more positive than negative emotional reactivity (or vice versa) compared with those who recover.…”
Section: Resultsmentioning
confidence: 99%
“…T here has been considerable empirical study of, as well as speculation regarding, the possible relation between emotion and childhood stuttering (e.g., Adams, 1992;Bloodstein, 1949;Choi, Conture, Walden, Lambert, & Tumanova, 2013;Conture, Kelly & Walden, 2013;Guitar, 2014;W. Johnson et al, 1959;Jones, Choi, Conture, & Walden, 2014;Yairi, 1997).…”
mentioning
confidence: 99%
“…The latter result suggests that underlying variables, such as less distractibility, are involved in speech-language dissociations for at least a subgroup of preschool-age CWS. Given the present methodology (e.g., parent questionnaires and correlational analyses), it is difficult to determine the directionality of effect-that is, whether ineffective distractibility caused, resulted from, or simply co-occured with CWS's speech-language dissociations (see Conture, Kelly, & Walden, 2013, for a similar discussion about directionality of effect regarding temperament and speech-language disorders). Nevertheless, the present findings emphasize the importance of studying associations and interactions among multiple variables (e.g., dissociations across several speechlanguage domains in addition to distractibility) and their possible relation to childhood stuttering.…”
Section: Discussionmentioning
confidence: 99%
“…2,[4][5][6][7][8][9] Some of the identified personality characteristics, several measured by the Minnesota Multiphasic Personality Inventory, are: temperament, extraversion, introversion, neuroticism, type A personality (ambitious, rigidly organized), type D personality (negative affectivity), social inhibition, social alienation, social competence, loneliness, interpersonal sensitivity, self-confidence, perfectionism, diffuse anxiety, control of emotions, impulsivity, suspiciousness, obsessivecompulsive trait, coping style, pessimism (dissatisfaction, sadness), and tendency toward denial. 4,5,[10][11][12][13][14][15][16][17] In recent years, evidence has been found that FD is at least correlated with depressive symptoms and general anxiety, 5,18-21 but probably also with high neuroticism and hypochondriasis. 1,4 But correlation does not imply causation.…”
Section: The Search For Psychosocial Causes Of Fdmentioning
confidence: 99%